IDENTIFIKASI GENOTIPE MELON (Cucumis melo L.) TAHAN TERHADAP PENYAKIT GUMMY STEM BLIGHT (GSB) - Huda, Amalia Nurul; Ardela Nurmastiti; Rima Margareta Retnyo Gumelar; Nailan Nabila; Akhmad Izzul Farkhi; Eni Ismawati; Azeezah Mutiarani Rossi Hartanto; Osama Bintang (Jurnal Pertanian Agros, 2025)
The development of melon varieties (Cucumis melo L.) is not only carried out on improving fruit quality, but also on disease resistance, one of which is gummy stem blight (GSB). Gummy stem blight disease at high levels cause a decrease in quality to loss of yield, so the development of gummy stem blight-resistant varieties is necessary. The study was conducted in July - November 2024 in Desa Bansari, Kecamatan Bansari, Kabupaten Temanggung, Central Java Province. The design used was a single-factor complete randomized block design (RCBD) with three replications using 21 melon genotypes planted in a greenhouse. Based on the incidence and severity of gummy stem blight disease observed in the generative phase through natural infection, it is known that there are very significant differences between the test genotypes. In this experiment, no genotypes were found to be highly resistant to gummy stem blight. Potential genotypes that showed moderate to low levels of disease incidence and severity included genotypes 44 (disease incidence: 53.33% and disease severity: 26%), 27 (disease incidence: 75.00% and disease severity: 25.33%), and 35 (disease incidence: 70.25% and disease severity: 37.00%). The broad-sense heritability values showed high values of 88.9% for disease incidence and 93.9% for disease severity. Potential genotypes from screening could be used in the development of lines for gummy stem blight resistance breeding.